COMPARISON OF LEVOBUNOLOL 0.5% WITH BRIMONIDINE 0.2% TO PREVENT MEAN INTRAOCULAR PRESSURE ELEVATION AFTER NEODYMIUM: YATRIUMALUMINIUM GARNET LASER CAPSULOTOMY: Yatrium-Aluminium Garnet Laser Capsulotomy - ., Dr Asfandyar; Manzoor, Muhamad; Ali, Dilshad; Murtaza, Bilal; Naqvi, Abid (Pakistan Armed Forces Medical Journal, 2018)
Objective: The objective was to compare 0.5% levobunolol with 0.2% brimonidine in terms of mean reduction of intraocular pressure to prevent post neodymium: Yatrium-aluminium garnet (Nd:YAG) laser capsulotomy pressure spike. Study Design: Randomized controlled trial. Place and Duration of Study: The study was conducted at Ophthalmology Department of Combined Military Hospital Peshawar from Mar 2014 to Sep 2014. Material and Methods: A total of 190 patients (95 in each group) were included in this study. In group-1 and group-2 patients, one drop brimonidine 0.2% and levobunolol 0.5% was instilled one hour before the Nd:YAG laser capsulotomy, respectively. Posterior capsulotomy was carried out with Nd:YAG laser. One drop of the respective drug instilled just after the laser treatment to each group. Intraocular pressure was measured with goldman applanation tonometer (GAT) 2 hours after Nd:YAG laser capsulotomy. Results: Mean age was 62.64 ± 4.48 years for group-1 and 62.76 ± 4.50 years for group-2. Gender distribution was as follows: 56 patients (59.0%) were male and 39 patients (41.0%) were female in group-1 while 59 patients (62.1%) were male and 36 patients (37.9 %) were female in group-2. In group-1 baseline mean IOP was 13.72 ± 2.24 and in group-2 it was 13.94 ± 1.98 (p=0.474). At 2 hours post YAG, IOP was 14.92 ± 2.21 and 15.85 ± 1.98 in group-1 and group-2, respectively (p=0.003). Conclusion: Present study provide substantial evidence in favour of brimonidine for prevention of rise in IOP after Nd:YAG laser posterior capsulotomy.